Giant paleoburrows in the Porto Alegre metropolitan area (state of Rio Grande do Sul, Brazil) - Frank, Heinrich Theodor; Buchmann, Francisco Sekiguchi [UNESP]; de LIMA, Leonardo G.; Caron, Felipe; Lopes, Renato Pereira; Fornari, Milene [UNESP] (Universidade Federal do Rio Grande do Sul, 2023)
Tunnels dug by semi-fossorial mammals of the South American Cenozoic megafauna are known as paleoburrows and are generally described from isolated records or very restricted regions. A particularly favorable set of conditions allowed the systematic mapping of paleoburrows over more than a decade in the Porto Alegre metropolitan area (Rio Grande do Sul state, Brazil), covering more than 10,000 km2. Through digital prospecting, media strategies, and fieldwork, more than 400 paleoburrows were found in this region, usually in large-scale anthropogenic excavations. The structures may consist of a single one or several tunnels, reaching up to two or three dozens. Burrows can be open or filled with sediments to a variable extent. More than 80% of the tunnels are filled with sediment, thus classified as crotovines. Their widths range between 0.5 and 3.0 m and their heights are between 0.5 and 2.0 m. Tunnels with a diameter of 1.4 m, with original estimated lengths of more than 50 m, are frequent. Excavation traces on burrow walls and roofs are common, but fossils have not been found. In very flat areas like floodplains or areas with very uneven relief (mountainous), paleoburrows are rare to absent. The largest amount of tunnels was found in regions of hilly and relatively stable relief, dug in different lithotypes except unconsolidated sediments or unaltered magmatic or metamorphic rocks. It is possible that each hill may have several paleoburrows, isolated or in groups, around its base. Thus, the region can be considered the one with the highest known density of paleoburrows of this type in the world so far.
Paleotocas gigantes na Região Metropolitana de Porto Alegre (estado do Rio Grande do Sul, Brasil)
Keywords: Crotovines; Ichnofossils; Megafauna; Megaichnus